Key Factors Affecting Junior College Students' Satisfaction and Loyalty Towards a Social Networking Services Platform in Chengdu, China - Zhonghui, Shu (Scholar: Human Sciences, 2025)
Purpose: This article aims to research the critical factors impacting junior college students’ satisfaction and user loyalty when using a social networking platform. The conceptual framework demonstrates the causal relationship between Perceived usefulness, Perceived ease of use, Trust, Utilitarian Value, Hedonic Value, Satisfaction, and User Loyalty. Research design, data, and methodology: The researchers used a quantitative technique (n=500) to administer the questionnaire to senior college students in Chengdu, China. Non-probability sampling included judgmental sampling to select the four majors of Sichuan Vocational and Technical College of Communications, quota sampling to determine the sample size, and convenience sampling to collect data and distribute questionnaires online. The researchers used structural equation modeling (SEM) and validation factor analysis (CFA) to analyze the data, including model fit, reliability, and structural validity. Results: Perceived usefulness, perceived ease of use, trust, utilitarian value, and hedonic value had a significant effect on satisfaction, and satisfaction was used as an intermediate variable affecting user loyalty. Perceived ease of use has the greatest effect on satisfaction, followed by perceived usefulness. Conclusions: This study has important theoretical and practical value for improving the user experience of students using the social networking services platform in Chinese higher vocational colleges and universities.